Evaluation of Different Rice Genotypes under Aerobic Conditions - Pasha, Md. Latheef; Bhadru, D.; Krishna, L.; Naik, R. B. M. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted at Agricultural Research station, Kampasagar, Nalgonda district of Andhra Pradesh during kharif 2008-09 to screen rice varieties suitable for aerobic rice cultivation. 12 rice varieties viz., MTU 1001, MTU 1010, JGL 11727, BPT 5204, JGL 384, Tellahamsa, RNRM-7, JGL 3844, Erramallelu, JGL 1798, JGL 3828 and JGL 3855 were evaluated in a randomized block design with three replications. The rice variety JGL 11727 produced the highest grain yield of 6.18 q ha-1and it was significantly superior to other rice varieties except JGL 3855 which produced on par grain yield (6.16 q ha-1). The next best variety was MTU 1010 (5.33 q ha-1) and was on par with JGL 1798 (5.21 q ha-1), JGL 384 (5.18 q ha-1) and RNRM-7 (5.00 q ha-1). The combined amount of effective rainfall and irrigation water from sowing to harvest varied from 775 to 900 mm. The variety JGL 11727 with duration of 130 days registered the highest water use efficiency of 7.3 kg rice ha-1 mm of water. Tellahamsa, which matured in 115 days, recorded the lowest water use efficiency of 3.5 kg of rice ha-1 mm of water. The second best variety was JGL 3855 (7.1 kg ha-1 mm-1). Highest BC ratio of 2.0 was recorded in JGL 11727 and JGL 3855 followed by BPT 5204 and JGL 1798 (1.7). Lowest BC ratio was obtained in Tellahamsa.